A genetic variant in NRP1 is associated with worse response to ranibizumab treatment in neovascular age-related macular degeneration. Issue 1 (January 2016) - Lorés-Motta, Laura; van Asten, Freekje; Muether, Philipp S.; Smailhodzic, Dzenita; Groenewoud, Joannes M.; Omar, Amer; Chen, John; Koenekoop, Robert K.; Fauser, Sascha; Hoyng, Carel B.; den Hollander, Anneke I.; de Jong, Eiko K.
Abstract : Objective: The aim of the study was to investigate the role of single-nucleotide polymorphisms (SNPs) located in the neuropilin-1 ( NRP1 ) gene in treatment response to antivascular endothelial growth factor (VEGF) therapy for neovascular age-related macular degeneration (nvAMD). Methods: Four SNPs in the NRP1 gene (rs2229935, rs2247383, rs2070296, and rs2804495) were genotyped in a study cohort of 377 nvAMD patients who received the loading dose of three monthly ranibizumab injections. Treatment response was assessed as the change in visual acuity after three monthly loading injections compared with baseline. Results: SNP rs2070296 was associated with change in visual acuity after 3 months of treatment. Patients carrying the GA or AA genotypes performed significantly worse than individuals carrying the GG genotype ( P =0.01). A cumulative effect of rs2070296 in the NRP1 gene and rs4576072 located in the VEGF receptor 2 ( VEGFR2 or KDR ) gene, previously associated with treatment response, was observed. Patients carrying two risk alleles performed significantly worse than patients carrying zero or one risk allele ( P =0.03), and patients with more than two risk alleles responded even worse to the therapy ( P =3×10 –3 ). The combined effect of these two SNPs on the response was also seen after 6 and 12 months of treatment. Conclusion: This study suggests that genetic variation in NRP1, a key molecule in VEGFA-driven neovascularization, influences treatment response to ranibizumab in nvAMD patients. The results of this study may be used to generate prediction models for treatment response, which in the future may help tailor medical care to individual needs. Abstract : Supplemental Digital Content is available in the text.